Tortillas and Tomatoes: Transmigrant Mexican Harvesters in Canada - Basok, Tanya (McGill-Queen's University Press, 2002)
An exploration of the vital role played by Mexican seasonal workers in Canadian agriculture and how they have become a structural necessity in some sectors. Based on interviews with Leamington greenhouse growers and migrant Mexican workers, Tanya Basok offers a timely analysis of why the Seasonal Agricultural Workers Program is needed. She argues that while Mexican workers do not necessarily constitute cheap labour for Canadian growers, they are vital for the survival of some agricultural sectors because they are always available for work, even on holidays and weekends, or when exhausted, sick, or injured. Basok exposes the mechanisms that make Mexican seasonal workers unfree and shows that the workers' virtual inability to refuse the employer's demand for their labour is related not only to economic need but to the rigid control exercised by the Mexican Ministry of Labour and Social Planning and Canadian growers over workers' participation in the Canadian guest worker program, as well as the paternalistic relationship between the Mexican harvesters and their Canadian employers. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/tortillastomatoe0000baso
Keywords: Foreign workers; Mexican; Ontario. Agricultural laborers; Foreign; Ontario. Agricultural laborers; Foreign. Foreign workers; Mexican; Ontario. Trabajadores extranjeros mexicanos; Ontario. Travailleurs agricoles étrangers; Ontario. Travailleurs étrangers mexicains

Colonization and Community: The Vancouver Island Coalfield and the Making of the British Columbian Working Class - Belshaw, John Douglas (McGill-Queen's University Press, 2002)
An examination of the social, political, and demographic history of British miners and their households on Vancouver Island in the nineteenth century. In the nineteenth century coal-miners imported from Europe, Asia, and eastern North America burrowed beneath the Vancouver Island towns of Nanaimo, Wellington, and Cumberland. No group was as numerous and influential in this enterprise as the hundreds of British immigrants who traveled half-way around the world to take up back-breaking work in the most remote colony in the Empire. What drew the British miners and their families to the north Pacific? Why did they set aside six months to journey to a colony about which they knew little? Once they reached Vancouver Island, what did they make of it and what did they make it into? And how did they re-make themselves in the process? In Colonization and Community John Belshaw takes a new look at British Columbia's first working class, the men, women, and children beneath and beyond the pit-head. Beginning with an exploration of emigrant expectations and ambitions, he investigates working conditions, household wages, racism, industrial organization, gender, schooling, leisure, community building, and the fluid identity of the British mining colony, the archetypal west coast proletariat. By connecting the story of Vancouver Island to the larger story of Victorian industrialization, he delineates what was distinctive and what was common about the lot of the settler society. Belshaw breaks new ground, challenging the easy assumptions of transferred British political traditions, analyzing the colonial at the household level, and revealing the emergent communities of Vancouver Island as the cradle of British Columbian working-class culture. –Publisher's description

Labour Law in Canada - Carter, Donald D.; England, Geoffrey; Etherington, Brian; Trudeau, Gilles (Wolters Kluwer, 2002)
For a clear understanding of the legal protections and remedies available to employers and workers in Canada, this convenient survey and analysis is ideal. Although it may be said that there are eleven distinct systems of labour law in Canada - encompassing ten provinces and the Federal government - the authors ensure depth of treatment by focusing on common policy themes and typical legal solutions, with significant departures noted in whatever province or area of law they may arise. However, the relevant law of the three most populous and influential provinces - Quebec, Ontario, and British Columbia - is covered in particular detail, as is Federal labour legislation and case law. Among the important areas of Canadian law and practice emphasised are the following: the tension between trade union power and business flexibility; collective "labour law" and individual "employment law"; the effect of the North American Free Trade Agreement; the central place of the legal concept of the employment contract; labour standards legislation; the influence of the 1982 Charter of Rights and Freedoms; court intervention in labour law, both under common law principles and Quebec's civil code; the role of labour relations boards; and judicial review of administrative decisions and arbitration awards. As an accurate and usable guide for lawyers not expert in Canadian law, Labour Law in Canada is without peer. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/labourlawincanad0000cart
Keywords: Bargaining; Collective Agreements; Labour Movement; Labour law; Trades; Unions

Bienfait: The Saskatchewan Miners' Struggle of '31 - Endicott, Stephen Lyon (University of Toronto Press, 2002)
Against all odds, the miners of Bienfait, Saskatchewan, attempted, in 1931, to change their miserable situation by organizing a union. Exploring the social consequences of capitalist restructuring during the Great Depression, Stephen Endicott focuses on the miners' tumultuous thirty-day strike. Their bid to gain union recognition with the aid of the Workers' Unity League of Canada ultimately failed, and Endicott's in-depth examination of the key factors and players attempts to explain why this was the case and why a similar union drive a decade later succeeded." "Based on a large number of both oral and written primary resources, Bienfait offers a new interpretation of the role of corporations, governments, courts, and the police in the events surrounding the strike. In the process, Endicott demonstrates how a militant union leadership helped the workers gain the strength and unity of purpose to challenge the powers of wealth and deep-seated prejudice. Bienfait opens a new chapter in the history of Canadian labour relations that reveals much about Canadian and Canadian society during the Depression. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/bienfaitsaskatch0000endi
Keywords: Coal Miners' Strike; Estevan; Sask.; 1931.; Grève des mineurs de charbon; Estevan; Sask.; 1931

Cabbagetown: The Classic Novel of the Depression in Canada - Garner, Hugh (McGraw-Hill Ryerson, 2002)
Toronto's Cabbagetown in the Depression...North America's largest Anglo-Saxon slum. Ken Tilling leaves school to face the bleak prospects of the dirty thirties-where do you go, what do you do, how do you make a life for yourself when all the world offers in unemployment, poverty and uncertainty?"As a social document, Cabbagetown is as important and revealing as either The Tin Flute or The Grapes of Wrath. Stern realism has also projected upon the pages of a whole gallery of types, lifelike and convincing. He is well fitted to hold the mirror up to human nature." Globe and Mail.Cabbagetown was first published in an abbreviated paperback edition in 1950 and was published in its entirety in 1968. This, the first quality paperback edition, contains the full unexpurgated text of Cabbagetown. –Publisher's description
Keywords: Poor; Poverty; Slums; Social Class and Equality; Toronto (Ont.); Unemployment

Their Own History: Women's Contribution to the Labour Movement of British Columbia - Griffin, Betty; Lockhart, Susan (United Fishermen & Allied Workers Union/CAW Seniors Club, 2002)
The United Nations declared 1975 International Women's Year for the purpose of promoting equality of men and women.... Canada alloted funds for projects aimed at achieving these objectives and many projects were undertaken across the country. The Central Council of Women's Auxiliaries to the United Fishermen & Allied Workers' Union at its annual convention in 1975 undertook to write a history highlighting women's contribution to the trade union movement in British Columbia. Finally, here is that book. Working people in BC have a proud history: a history that accalims the struggles for a better life, a better job and a better community. In 1975, we set out to record the history of the women of British Columbia who struggled for human rights and women's equality and who helped build our trade unions. We interviewed and recorded a wonderful group of women and men. And we appreciated all their stories. [This book] shares those stories. –Publisher's description
OCLC: 49513517
Keywords: Biographies; British Columbia; Femmes Travail Colombie-Britannique Histoire; Femmes dans le mouvement ouvrier Colombie-Britannique Histoire; History; Personnel féminin Colombie-Britannique Biographies; Women Employment; Women Employment British Columbia History; Women employees; Women employees British Columbia Biography; Women in the labor movement; Women in the labor movement British Columbia History

Is Anyone Listening?: Women, Work, and Society - Jacobs, Merle; Armstrong, Pat; Armstrong, Hugh; Bannerji, Himani; Hagey, Rebecca; MacKay, Robert W.; Ng, Roxana; Gupta, Tania Das; George, Usha; Bruckert, Chris; Kirk, Jo-Anne; Daenzer, Patricia; et al. (Women's Press, 2002)
Jacobs has brought together the work of a number of progressive feminist writers, who theorize gender, race, diversity research, the social construction of women and work, ethnicity and class. The essays in this reader are focused on issues relating to gender equality in workspaces in society. The editor has gathered essays from well-known and established social scientists. Among them are Pat and Hugh Armstrong, Himani Bannerji, Christine Bruckert and Tania Das Gupta. The result is a stimulating collection that focuses on health-care workers, teachers, strippers, wage-less workers and women who are hidden from view. The collection explores the construction of gender, the selection of careers and the differential in work conditions and wages. –Publisher's description. Contents: Theorizing women's work: feminist methodology / Pat Armstrong and Hugh Armstrong – The paradox of diversity: the construction of a multicultural Canada and "women of colour" / Himani Bannerji – Qualitative research to identify racialist discourse: towards equity in nursing curricula / Rebecca Hagey and Robert W. MacKay – Teaching against the grain: contradictions and possibilities / Roxana Ng – Racism in nursing / Tania Das Gupta – Toward anti-racism in social work in the Canadian context / Usha George – The world of the professional stripper / Chris Bruckert – Gender inequality and medical education / Jo-Anne Kirk – Benevolent patriarchy: the foreign domestic movement, 1980-1990 / Patricia Daenzer – The new wageless worker: volunteering and market-guided health care reform / Elizabeth Esteves – "Who else would do it?": female family caregivers in Canada / Kristin Blakely – Marginal women: examining the barriers of age, race and ethnicity / Robynne Beugebauer – Creating understanding from research: staff nurses' views on collegiality / Merle Jacobs – Antiracism advocacy in the climate of corporatization / Rebecca Hagey, Jane Turrittin, Evelyn Brody – Undertaking advocacy / Merle Jacobs.
https://www.canadianscholars.ca/books/is-anyone-listening#tab_overview

Harnessing Labour Confrontation: Shaping the Postwar Settlement in Canada, 1943-1950 - McInnis, Peter S. (Peter Stuart) (University of Toronto Press, 2002)
The 1940s in Canada are crucial to the understanding of labour history in this country. Following the Depression, and sparked by the need to mobilize the workforce during the Second World War, this decade led to a restructuring of the relationship between labour and the state. In Harnessing Labour Confrontation, Peter S. McInnis examines the reformation of Canadian society and its industrial relations regime from the perspective of labour organizations and their supporters and from that of government and business. What results is a synthesis of labour and political history, which the author uses to analyze in a North American context the role of confrontation and heated debate in the formation of a national postwar compromise and in the birth of a modern welfare state.Among the factors affecting the postwar compromises were, argues McInnis, the divided jurisdiction between federal and provincial governments, the return to gender-biased societal norms, a developing Cold War climate of national insecurity, and a promise of strong consumer purchasing power based on postwar wages and benefits packages. While some of the results of the 1940s compromise and the welfare state remains intact today, many of the political and social structures have deteriorated in the last two decades. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/harnessinglabour0000unse https://utorontopress.com/ca/harnessing-labour-confrontation-3

Cows Don't Know It's Sunday: Farming in St. John's - Murray, Hilda Chaulk (Memorial University Press, Institute of Social and Economic Research, 2002)
Before 1950, the greatest number of Newfoundland farmers lived in the St. John's area. They and the townsfolk were interdependent, with the farmers providing meat, poultry, garden and dairy products to the city, while St. John's served as a ready market and a source of cash income. Although many street names serve as reminders of those who once worked the land, and others perpetuate old homesteads, the farmers of St. John's are as unknown today as though they had never been. Cows Don't Know It's Sunday gives a historical overview of farming and its importance to the economy of Newfoundland, and describes in detail, using the words of more than eighty people who grew up on or near farms, what it was like to farm in and around St. John's in the period within living memory. Farmers worked seven days a week throughout the year. This study of both the work life and social life of the farmers of St. John's is a tribute to the farming families who were the mainstay of the city during the first half of the twentieth century. –Publisher's description
OCLC: 51295723

The Contested Past: Reading Canada's History: Selections from the Canadian Historical Review - Shore, Marlene (University of Toronto Press, 2002)
This collection of selected excerpts focuses on the Canadian Historical Review's contribution to the study of Canadian history from the journal's founding in 1920 to the present. Using the CHR's own interconnected objectives as a benchmark - the promotion of high standards of historical research and writing in Canada, and the fostering of the study of Canadian history - Marlene Shore analyses the varying degrees of success the journals had in meeting its those goals. Her introductory essay shows how the CHR was shaped not only by its own editorial policies, but by international currents affecting the discipline of history and its practitioners. The excerpts, each accompanied by critical commentary, were chosen as representative of the major trends, crucial studies, and main controversies in Canadian historical writing. Shore has arranged them chronologically and thematically into four sections: Nation and Diversity, 1920-1939; War, Centralization, and Reaction, 1940-1965; The Renewal of Diversity, 1966 to the Present; and Reflections. Among the key themes explored by Shore and the contributing historians, Native-European contact, society and war, the nature of Canadian and Quebec nationalism, class-consciousness, and gender politics are highlighted. Broad in scope and focused in intent, The Contested Past offers an excellent introduction to twentieth century Canadian history and historiography. –Publisher's description
Book available at Internet Archive to people with print disabilities: http://archive.org/details/contestedpastrea0000unse
Keywords: Canada – Historiography

Contingent Work, Disrupted Lives: Labour and Community in the New Rural Economy - Winson, Anthony; Leach, Belinda (University of Toronto Press, 2002)
[E]xamines the effects of economic globalization on several manufacturing-dependent rural communities in Canada. In looking at such contemporary corporate strategies as plant closures and downsizing, authors [The authors] consider the impact of capitalist restructuring on the residents of various communities. [They] argue that the new rural economy has caused considerable instability and hardship in the lives of rural residents as they struggle to adapt in the face of economic upheaval."–Publisher's description. Contents: The Global and the Local: Understanding Globalization through Community Research – Community Sketches, History, and Method – The New Rural Economy and the Shape of Restructuring – Skidding into the Contingent Work World – 'Forget All Your Dreams and Good Luck with Your Life': Lay-Off and the New Reality of Contingent Labour – Economic Diversity, Sustainability, and Manufacturing Communities. Geographic: Ontario. Ontario. Includes bibliographical references (pages 205-220) and index.
Book available at Internet Archive to people with print disabilities: https://archive.org/details/contingentworkdi0000wins_w9e7
Keywords: Aspect social; Ontario. Chômage en milieu rural; Ontario. Deindustrialization; Ontario. Deindustrialization. Displaced workers. Globalization; Ontario. Desempleo; Ontario. Displaced workers; Ontario. Désindustrialisation; Ontario. Globalization; Ontario. Industrie rurale; Ontario. Mondialisation; Ontario. Rural industries; Ontario. Trabajadores; Ontario. Travailleurs; Ontario. Travailleurs licenciés; Ontario. Working class; Rural unemployment; Social aspects; Social aspects. Rural industries. Rural unemployment. Working class. Landwirtschaft. Arbeitslosigkeit